2014
DOI: 10.1188/14.cjon.239-241
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluating the Neutropenic Diet: Time to Change

Abstract: The neutropenic diet historically has been a mainstay in oncology practice, with many providers continuing to adhere tightly to the diet for patients with neutropenia. However, clinically sound evidence remains limited and weak and does not support the diet as a foundation for policy and practice. Therefore, two questions remain: Does evidence exist to support the effectiveness of the neutropenic diet in reducing infection rates in the neutropenic oncology population? Based on limited evidence supporting the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Only little evidence support a neutropenic diet to prevent infection for patients undergoing chemotherapy or radiotherapy, as the only few randomized control trials performed used variable methodologies and presented several limitations [ 79 , 80 ]. Indeed, a neutropenic diet may impose unnecessary food restrictions on patients who often consume insufficient dietary intakes [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only little evidence support a neutropenic diet to prevent infection for patients undergoing chemotherapy or radiotherapy, as the only few randomized control trials performed used variable methodologies and presented several limitations [ 79 , 80 ]. Indeed, a neutropenic diet may impose unnecessary food restrictions on patients who often consume insufficient dietary intakes [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several authors have recommended that safe food handling procedures should be prioritized over a restricted neutropenic diet for immunocompromised patients. 3,6,20 Additionally, a review article by Fox and Freifeld highlighted that the first etiology of foodborne illness is unsafe handling of food, and that the available evidence fails to demonstrate that a neutropenic diet is free of food pathogens. 18 They further emphasize that there is insufficient evidence to address the hypothetical role of a neutropenic diet in preventing foodborne illnesses.…”
Section: Neutropenic Diets Commonly Exclude Vegetables and Fruits Basedmentioning
confidence: 99%
“…In general, this diet excludes raw fruits and vegetables based on the concept that some foods have a greater microbiological load that could be harmful . However, there is no scientific evidence to support its benefit, and this diet can lead to difficulties in compliance and oral intake . Moreover, the lack of knowledge regarding the neutropenic diet has led to a lack of uniformity in the dietary recommendations of centers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are still contradictory results about its efficacy [4][5][6][7][8][9][10][11][12] . The studies have suggested that raw and cooked diet have no effect on the infection incidence [4][5][6][7][8][9][10][11][12][13][14][15][16] and patients who adhere from the cooked dietary pattern, the principal of neutropenic diet, have significantly lower vitamin C intake (38.9%). Moreover, the level of vitamin C decreases in blood malignancies 17 .…”
Section: Introductionmentioning
confidence: 99%